Winterkeep - Cashore, Kristin (Cashore, Kristin. Graceling Realm book., 2021)
"Queen Bitterblue of Monsea must head to the nation of Winterkeep after her envoys drown in suspicious circumstances, and somewhere there, Lovisa Cavenda waits and watches while tragedy with devastating political and personal ramification strikes."--